Analysis of Printed Circuit Boards strains using finite element analysis and digital image correlation (Fracture and Structural Integrity, 2019)
This paper investigates the use of digital image correlation (DIC) and finite element analysis for strain measurement on Printed Board Circuits (PCBs).Circuit boards (PCBs) are designed to mechanically support and electrically connect an electronic component assembly. Due to screw assemblies, the surface level differences on which the PCB is placed, the process of assembling the electronic components induces a certain state of stress and deformation in the PCB. The main components affected are microprocessors due to the way they are glued to PCBs with BGA - Ball grid arrays (BGA).Digital Image Correlation (DIC) is a full-field contactless optical method for measuring displacements and strain in experimental testing, based on the correlation of images taken during test. The experimental setup is realized with Dantec Q-400 system used for image capture and Istra 4D software for image correlations and data analyses. The maximum level of the obtained strain is compared with the allowable limit.Finite element analysis (FEA) is a numerical method of analysis for stresses and strain in structures of any given geometry.
Keywords: Digital image correlation; Finite element analysis; PCB; strain